Penguatan daya saing pemerintahan desa untuk pembangunan berkelanjutan: Studi Kasus pendampingan di Desa Manunggal - Muhajir, Ahmad; Nasution, M. Afif Herliandi; Manalu, Simon Patar Rizki; Marlina (LPPM Universitas Al-Azhar medan, 2025)
Achieving the Sustainable Development Goals (SDGs) is a significant challenge for many villages in Indonesia, including Desa Manunggal in Labuhan Deli Subdistrict, Deli Serdang Regency. The Community Service Program (PKM) implemented by the University of Al-Azhar Medan aims to support the acceleration of SDGs achievement through assistance in managing village governance competitiveness. Desa Manunggal was chosen due to its substantial potential, although it faces challenges in optimizing these resources. The primary objective of this study is to enhance village competitiveness through improved managerial capacity and resource management based on SDG principles, involving community empowerment and strengthening village institutions.The research uses a participatory approach, involving training on village competitiveness management and direct assistance to village officials and the community. This program was carried out in three phases: preparation, training, and implementation, with collaboration between faculty members, students, and village government. The novelty of this study lies in integrating the SDGs concept into every phase of the program, prioritizing sustainable resource management through strengthening village governance and local economic empowerment, including SMEs and Village-Owned Enterprises (BUMDesa).The findings of this study show that the PKM program successfully improved the village government's capacity to manage resources and foster sustainable economic development. Active community participation in this program has had a positive impact on SDG management at the village level, improving the quality of life and strengthening transparent and participatory governance